Blockchain: a game changer in electronic waste management in India. (14th May 2021) - Chaudhary, Karishma; Padmanabhan, Prasanna; Verma, Deepak; Yadav, Prashant Dev
In 2016, 44.7 million metric tonnes of electronic waste (e-waste) was generated across the globe out of which only 20% was recycled through formal channels. India is the fifth largest generator of e-waste where 95% of e-waste is channelised to unorganised units. There are substantial environment and health risks associated with unsafe e-waste management practices. The study highlights various blockchain-based applications in the waste management domain. The study deals with the development of Ethereum-based smart contract blockchain architectural platform 'e-waste lens' for effective e-waste management in India. The specific novelty of the blockchain architectural framework lies in the real-time tracking and monitoring of e-waste movement by the concerned stakeholders in the e-waste management chain and thereby bringing out the non-compliance of the prevailing regulations for effective e-waste management.